Design of Output LCL Filter for 15-level Cascade Inverter - Pastor, M.; Dudrik, J. (Elektronika ir Elektrotechnika, 2013)
This paper presents the design procedure for the output LCL filter used in grid connected one-phase 15-level cascade voltage source inverter for photovoltaic application. Output power of a system is in kilowatt range due to one-phase connection. The filter design is based on detailed analysis as it is a multifold problem. Design is adopted for predictive current control technique with finite control set. Because of lack of modulation technique there is no detailed higher-order harmonic analysis. Key parameters that define filter performance are described. Step-by-step design of LCL filter is presented. The design procedure is done in pre-unit base so results can be used for wider range of power levels. No passive damping is considered as active damping is preferable with regard to high efficiency of photovoltaic inverter. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5394